Socio-demographic differences in energy drink consumption and reasons for consumption among US college students. (April 2016) - Poulos, Natalie S; Pasch, Keryn E
Background: Energy drink consumption has become increasingly prevalent among US college students, yet little is known about current rates of consumption and reasons for consumption among current energy drink users, particularly differences related to gender and race/ethnicity. Objectives: To better understand energy drink consumption alone and mixed with alcohol among US undergraduate college students who currently use energy drinks. Methods: Participants included 330 energy drink users ( m age = 18.7; White = 48.5%; Women = 46.1%) and 229 energy drink mixed with alcohol users ( m age = 18.8; White = 51.5%; Women = 51.8%). Students completed an online survey, which measured energy drink consumption alone and energy drinks mixed with alcohol. Descriptive statistics and differences by race/ethnicity and gender are reported for patterns and reasons of use. Results: Among past year energy drink users, 64.9% consumed energy drinks in the past month and 38.5% consumed in the past week. The most common reasons for energy drink consumption alone included studying for an exam and taste. Among past year energy drink mixed with alcohol users, 31.9% consumed within the past month. The most common reasons to mix alcohol and energy drinks included taste and to hide the flavour of alcohol. Key findings include that young men consume energy drinks alone and mixed with alcohol more often than young women. Young men are more likely to report energy drink consumption in the past week and report reasons related to partying than young women, while non-White youth report reasons related to academic performance as compared to White youth. Conclusion: Consideration of patterns and reasons for energy drink consumption may help interventions to ensure appropriate behaviours are targeted and are relevant to the population.